2019
DOI: 10.32615/ps.2019.081
|View full text |Cite
|
Sign up to set email alerts
|

Influence of shading on photosynthesis and antioxidative activities of enzymes in apple trees

Abstract: This study investigated the effects of shading on photosynthesis in 3-year-old potted apple trees. The trees were grown either in full sunlight or in a shade environment with about 50% of sunlight filtered through black plastic nets. Under the shade conditions, the net photosynthetic rate (PN), the stomatal conductance, the transpiration rate, and the intercellular CO2 concentration decreased before midday, which was due to low light energy but the PN of the shaded trees increased relative to the control trees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…A similar effect was obtained by pruning trees [46,47]. Strongly sunny plants can be damaged by sunlight, too intense sun can inhibit photosynthetic processes [26,33,48]. The distance of 1 m between fruit trees resulted the most intensive photosynthesis activity.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…A similar effect was obtained by pruning trees [46,47]. Strongly sunny plants can be damaged by sunlight, too intense sun can inhibit photosynthetic processes [26,33,48]. The distance of 1 m between fruit trees resulted the most intensive photosynthesis activity.…”
Section: Discussionsupporting
confidence: 59%
“…During the growing season, the rate of photosynthesis mostly depends on the photoperiod; however, research showed that young leaves are more photosynthetically active during the long day, and the rate of photosynthesis decreases as the leaves age [26,30]. Significant decrease of stomatal conductance followed by transpiration rate in July and August was observed (Figure 2).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Considering medicinal plants yield and irrigation costs, evapotranspiration can play a guiding role in the cultivation of medicinal plants (Ahemd et al 2016). High light induced leaf temperature rise and excessive transpiration can lead to water deficit, decrease of photosynthetic rate and even plant death (Liu et al 2019. Over-shading also limits transpiration, which can limit photosynthetic rate and affect plant growth, too (Shao et al 2014).…”
Section: Discussionmentioning
confidence: 99%